Identifying Pre-Service Teachers’ Beliefs About Teaching EFL and Their Potential Changes (2017)
This study aims at identifying pre-service teachers’ beliefs about teaching English as a foreign language and tracking their potential changes throughout the teaching practicum. Participants were two pre-service teachers in their fifth year of their Bachelor of Arts in Foreign Languages program in a public university in Colombia. Data were gathered through a modified version of Beliefs about Language Learning Inventory before the practicum, eight weekly journal entries administered during ten weeks, and two semi-structured interviews at the end of the teaching practicum. The findings revealed that most of the pre-service teachers’ beliefs changed once they faced the reality of the classroom.